2003
DOI: 10.1016/s0002-9440(10)63550-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Semicarbazide-Sensitive Amine Oxidase in Smooth Muscle Cells Leads to an Abnormal Structure of the Aortic Elastic Laminas

Abstract: Elevated semicarbazide-sensitive amine oxidase (SSAO) activity has been observed in several human conditions, eg, diabetes, and it has been speculated that SSAO contributes to the development of vasculopathies associated with this disease. To investigate in vivo consequences of elevated expression of SSAO in vascular tissues, we have developed a transgenic model for overexpression of human SSAO in mice. A smooth muscle-specific promoter, smooth muscle alpha-actin promoter 8 (SMP8) was used. Transgenic expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 31 publications
3
54
1
Order By: Relevance
“…It has been reported that, in transgenic mice overexpressing SSAO in vascular smooth muscle cells, an abnormal structure of the aortic elastic lamellae is observed. 12 We have shown recently that in idiopathic annuloaortic ectasia disease, there was a dramatic downregulation in SSAO expression in the affected areas that was correlated with a reduction in elastic lamellar thickness. 19 Our results show that SCZ induced morphological alterations of elastic lamellae in the CA and a reduction in the amount of insoluble elastin, which corresponds with mature, crosslinked elastin.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that, in transgenic mice overexpressing SSAO in vascular smooth muscle cells, an abnormal structure of the aortic elastic lamellae is observed. 12 We have shown recently that in idiopathic annuloaortic ectasia disease, there was a dramatic downregulation in SSAO expression in the affected areas that was correlated with a reduction in elastic lamellar thickness. 19 Our results show that SCZ induced morphological alterations of elastic lamellae in the CA and a reduction in the amount of insoluble elastin, which corresponds with mature, crosslinked elastin.…”
Section: Discussionmentioning
confidence: 93%
“…The relation between soluble and membrane-bound human SSAO is not firmly established, but experiments with transgenic mice and rats strongly suggest that the major source of soluble SSAO is membrane-bound SSAO from endothelial cells and adipocytes [8,9]. Thus, it seems likely that the soluble form is formed from membrane-bound SSAO by shedding, as is the case for ACE [7,28].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that plasma SSAO is positively associated with level of glycaemic control, and confirmed that plasma SSAO activity is elevated, the more so in the presence of late complications, hypertension and ACEI therapy. The increasing evidence for SSAO having both deleterious effects in terms of cytotoxicity, AGE-formation, and oxidative stress [1,[3][4][5], and beneficial effects in terms of enhanced glucose uptake, proper formation of blood vessel walls, and anti-inflammatory functions [2,6,9] suggests the importance of regulatory factors to keep SSAO activity within narrow limits. The elevation of SSAO in diabetes could thereby be an adverse as well as a beneficial factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse SMAA promoter directed tissuespecific expression in all mammalian species thus far studied. [19][20][21][22][23][24][25][26] The purpose of this study was to evaluate the ability of this new construct to restore erectile function in an aging rat model of erectile dysfunction and to compare the results so obtained with that of our current construct, pVAX-hSlo. If the duration of action and efficacy are similar to preclinical studies with pVAXhSlo and pcDNA-hSlo, then the use of pSMAA-hSlo may confer additional therapeutic and regulatory advantages, namely, enhancement of the safety profile of Slo gene transfer by limiting its action to smooth muscle cells only.…”
Section: Introductionmentioning
confidence: 99%